Rapidly Progressive Classic Adamantinoma of the Spine: Case Report and Literature Review - Lou, Yan; Li, Ying; Xu, Lei; Jing, Xiaoping; Chen, Su; Yang, Minglei; Jiang, Hongyu; Zhao, Chenglong; Wei, Haifeng; Xiao, Jianru (Frontiers in Oncology, 2022)
Adamantinoma is a low-grade skeletal tumor, accounting for 0.5% of all primary bone tumors. The tumor usually progresses slowly, with a relatively promising prognosis. Primary or metastatic spinal adamantinoma of bone are rarer. Only four cases have been documented till date. We present two cases of aggressive spinal adamantinoma whose microphotography and radiographic appearance were unusual, with extensive involvement of multiple segments and rapid progression. Case 1 was a 36-year-old woman, presenting with back pain, progressive numbness and motor weakness, who was diagnosed with metastatic adamantinoma in the T2, T7, L2, and L4. She underwent spondylectomy three times to resect these lesions, respectively. Case 2 was a 68-year-old male with complaints of severe left back pain. MRI revealed destructive changes in T1-T4. He underwent posterior decompression (T1-T3), partial vertebrectomy (T2), fixation and fusion (C5-C7, T4-T6). The pathology of two patients was metastatic spinal adamantinoma. Rapid squamous progression was observed in specimens of T2 and T7 lesions of Case 1 in two months. Twenty-five months after surgery, Case 1 developed paralysis, but she refused to receive further examination and treatment. Two months after surgery, Case 2 presented with an upper back pain again. The MRI revealed an increase in osseous destruction and paravertebral mass size. He was administered radiotherapy, with his upper back pain partially relieved. The biological behavior of classic adamantinoma is highly unpredictable, often exhibiting more aggressive behavior upon recurrence or metastasis. The pathological diagnosis of adamantinoma should be confirmed by preoperative biopsy. En bloc resection with a wide margin is the preferred treatment for primary spinal adamantinoma. Radiation therapy can partially relieve the pain.